P1-S4.24 Balancing the "supply and demand" of sex acts: implications for modelling the HIV epidemic among men who have sex with men in Southern India. (10th July 2011) - Mitchell, K; Foss, A; Prudden, H; Williams, J; Johnson, H; Pickles, M; Phillips, A; Ramesh, B; Washington, R; Vickerman, P
Abstract : Background: In India, men who have sex with men (MSM) have distinct identities related to the role taken in anal sex (Panthi/Bisexual (PB): mostly insertive, Kothi/Hijra (KH): mostly receptive, Double Deckers: both). Wide discrepancies are found between the supply and demand for sex acts estimated for each group using data on reported frequency of anal sex, role taken and estimated group population sizes. Methods: Two methods for balancing the number and type of sex acts between different groups were compared. They were used in a deterministic HIV transmission model to estimate mixing patterns and HIV prevalence over the first 20 years of the epidemic (including reported condom use trends) and a subsequent 10-year intervention (10% absolute increase in condom use). Data collected from Bangalore for the evaluation of Avahan (the India AIDS initiative) on the mean reported frequency of sex acts per individual, role taken in anal sex and population sizes for each group were used to construct a mixing matrix. In method A, the PB group size was set to balance the total number of insertive and receptive acts, and receptive acts for each group were distributed among the three groups in proportion to the number of insertive acts offered. In method B, the proportion of receptive acts KH had with other KH was an additional input parameter, with remaining receptive acts distributed as in method A. The number and type of contacts for all groups were adjusted to achieve balancing. The model was run using 300 000 randomly sampled parameter sets drawn from the data and multiple fits were found to group-specific HIV prevalence data. Results: Model fits for method B had more assortative (like-with-like) mixing than method A, particularly for PB (median number of acts PB have with other PB: 48.5% (IQR 33.3–63.3%) in A, 63.3% (IQR 47.3–74.1%) in B), related to larger PB group sizes and PB taking the insertive role less often in B. Despite these differences, the fitted epidemic curves were very similar for all three groups across the two methods (Absrtact P1-S4.24 figure 1), as was the predicted intervention impact (relative reduction in MSM HIV prevalence after 10 years: A: 18.2% (95% CI 11.0 to 29.2%), B: 18.1% (10.6 to 29.7%)). Conclusions: The choice of method used to balance insertive and receptive contacts in an HIV transmission model affected the estimates for the amount of like-with-like mixing within different MSM groups, but the estimated impact of an intervention was robust to the method used.